2008
DOI: 10.1002/chp.192
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing a stroke assessment training workshop: Effectiveness, acceptability, and cost

Abstract: Clinicians participating in the TW via VC performed as well as those in the FTF group on the competency test. Videoconferencing improves access to CE, is well received by participants, and provides a cost-effective method of course delivery. Further evaluation of other CE events delivered through VC is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 18 publications
1
32
0
2
Order By: Relevance
“…Videoconferencing systems have experienced significant growth in recent years because of increased digital transmission options at reduced costs, vast improvements in video compression technologies, and improvements in the systems with an associated decrease in their cost. Several studies have Enhancing rural physician CME/CPD e503 demonstrated that CME/CPD videoconferencing is popular with rural physicians (Langille et al 1998;Davis & McCracken 2002;Klein et al 2005;Ricci et al 2005;Greenwood & Williams 2008), and is as effective, if not better, than faceto-face CME/CPD in increasing knowledge in a variety of clinical topic areas (Hampton et al 1994;Ricci et al 2005;Rossaro et al 2007;Miller et al 2008).…”
Section: Strategies To Enhance Cme/cpd Access For Rural Physiciansmentioning
confidence: 99%
“…Videoconferencing systems have experienced significant growth in recent years because of increased digital transmission options at reduced costs, vast improvements in video compression technologies, and improvements in the systems with an associated decrease in their cost. Several studies have Enhancing rural physician CME/CPD e503 demonstrated that CME/CPD videoconferencing is popular with rural physicians (Langille et al 1998;Davis & McCracken 2002;Klein et al 2005;Ricci et al 2005;Greenwood & Williams 2008), and is as effective, if not better, than faceto-face CME/CPD in increasing knowledge in a variety of clinical topic areas (Hampton et al 1994;Ricci et al 2005;Rossaro et al 2007;Miller et al 2008).…”
Section: Strategies To Enhance Cme/cpd Access For Rural Physiciansmentioning
confidence: 99%
“…Prior studies have shown success in videoconference-based training (Clifton, Byer, Heaton, Haberman & Gill, 2003). In a comparative study of face-to-face and videoconference-based training, no significant difference was found for clinicians (Miller et al, 2008) and patient interview (Kobak, Williams, Jeglic, Salvucci, & Sharp, 2008). Videoconferencing was also found to be successful for orthopedic consultations (Baruffaldi, Maderna, Ricchiuto, & Paltrinieri, 2004).…”
Section: Introductionmentioning
confidence: 73%
“…A qualidade do áudio/ vídeo e adequação da conexão são fatores que também interferem na opinião dos participantes quanto à utilização da videoconferência nestas atividades [9][10][11][12][13] . Outro fator importante foi a organização cuidadosa da atividade que envolveu a seleção adequada dos conteúdos, a utilização do material gráfico interativo e coerente aos conteúdos ministrados na capacitação, o recurso de aulas expositivas divididas em módulos com intervalos para perguntas, o uso de imagens e vídeos para ilustrar os conceitos a serem adquiridos e a presença do tutor na sala que recebeu o curso de educação permanente foram fatores que provavelmente também contribuíram para o êxito da atividade 26,27 .…”
Section: Discussionunclassified
“…Conclusão: a videoconferência foi uma ferramenta válida e aceita pelos profissionais estudados para ser utilizada em programas de capacitação em saúde auditiva infantil. A videoconferência como instrumento frente às atividades de educação permanente em saúde é recente no país [4][5] , mas experiências internacionais acumuladas até o presente momento evidenciaram não somente resultados positivos, com a mudança do comportamento do profissional após a capacitação, como também grande aceitação do recurso tecnológico para estas atividades [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Na Portaria SAS n o .…”
Section: Opinião Dos Agentes Comunitários De Saúde Sobre O Uso Da Vidunclassified